Comparison of osteogenic differentiation induced by siNoggin and pBMP-2 delivered by lipopolysaccharide-amine nanopolymersomes and underlying molecular mechanisms - Huang M (Dove Medical Press, 2019)
Mingdi Huang,1* Xinchun Zhang,1* Jing Li,2 Yanshan Li,1 Qinmei Wang,2 Wei Teng11Hospital of Stomatology, Guangdong Provincial Key Laboratory of Stomatology, Institute of Stomatological Research, Guanghua School of Stomatology, Sun Yat-sen University, Guangzhou, People’s Republic of China; 2Laboratory of Biomaterials, Key Laboratory on Assisted Circulation, Ministry of Health, Cardiovascular Division, First Affiliated Hospital, Sun Yat-sen University, Guangzhou, People’s Republic of China*These authors contributed equally to this work Purpose: Gene therapies via Noggin small interfering (si)RNA (siNoggin) and bone morphogenetic protein (BMP)-2 plasmid DNA (pBMP-2) may be promising strategies for bone repair/regeneration, but their ideal delivery vectors, efficacy difference, and underlying mechanisms have not been explored, so these issues were probed here.Methods: This study used lipopolysaccharide-amine nanopolymersomes (LNPs), an efficient cytosolic delivery vector developed by the research team, to mediate siNoggin and pBMP-2 to transfect MC3T3-E1 cells, respectively. The cytotoxicity, cell uptake, and gene knockdown efficiency of siNoggin-loaded LNPs (LNPs/siNoggin) were studied, then the osteogenic-differentiation efficacy of MC3T3-E1 cells treated by LNPs/pBMP-2 and LNPs/siNoggin, respectively, were compared by measuring the expression of osteogenesis-related genes and proteins, alkaline phosphatase (ALP) activity, and mineralization of the extracellular matrix at all osteogenic stages. Finally, the possible signaling pathways of the two treatments were explored.Results: LNPs delivered siNoggin into cells efficiently to silence 50% of Noggin expression without obvious cytotoxicity. LNPs/siNoggin and LNPs/pBMP-2 enhanced the osteogenic differentiation of MC3T3 E1 cells, but LNPs/siNoggin was better than LNPs/pBMP-2. BMP/Mothers against decapentaplegic homolog (Smad) and glycogen synthase kinase (GSK)-3β/β-catenin signaling pathways appeared to be involved in osteogenic differentiation induced by LNPs/siNoggin, but GSK-3β/β-catenin was not stimulated upon LNPs/pBMP-2 treatment.Conclusion: LNPs are safe and efficient delivery vectors for DNA and RNA, which may find wide applications in gene therapy. siNoggin treatment may be a more efficient strategy to enhance osteogenic differentiation than pBMP-2 treatment. LNPs loaded with siNoggin and/or pBMP-2 may provide new opportunities for the repair and regeneration of bone.Keywords: gene delivery, nanopolymersomes, Noggin, small interfering RNA, bone morphogenetic proteins, osteogenesis